Co-delivery of hydrophobic and hydrophilic drugs from erythrocyte-PLGA nanoparticles complex - Tan, Tabitha Su Teng. (2012)
This work reported the fabrication of a dual drug delivery system, where layer-by-layer polyelectrolyte-coated PLGA nanoparticles were attached onto the surface of erythrocyte via electrostatic attraction. PLGA nanoparticles were loaded with a model hydrophobic drug (ibuprofen) and coated with 3, 5 and 7 layers of polyelectrolyte. The coating successfully controlled the release of ibuprofen from PLGA nanoparticles while at the same time, rendered the PLGA nanoparticles with a positive surface charge which can bind to the erythrocyte having a negative surface charge. Besides this, the erythrocyte was also loaded with a model hydrophilic substance (FITC-dextran) and its release behavior was studied. Considering that the particles and RBCs behave as two independent systems, it was hypothesized that it is feasible to create a dual drug carrier that can carry both hydrophobic and hydrophilic drugs, at the same time. Circulation time of PLGA nanoparticles is also hoped to be enhanced by attachment onto the surface of erythrocyte.